Monocarboxylate transporter upregulation in induced regulatory T cells promotes resistance to anti-PD-1 therapy in hepatocellular carcinoma patients - Zhou, Jinren; Shao, Qing; Lu, Yunjie; Li, Yu; Xu, Zibo; Zhou, Bo; Chen, Qiuyang; Li, Xiangyu; Xu, Xiaozhang; Pan, Yufeng; Deng, Zhenhua; Wang, Yiming; et al. (Frontiers in Oncology, 2022)
Background: PD-1 immune checkpoint inhibitors are not effective in treating all patients with hepatocellular carcinoma (HCC) and regulatory T cells (Tregs) may determine the resistance to anti-PD-1 therapy. Methods: Patients were divided into two groups based on the clinical efficacy of anti-PD-1 therapy. Flow cytometry was used to determine the phenotype of CD4+, CD8+, and Tregs in peripheral blood mononuclear cells (PBMCs). CD4+CD45RA+T cells were sorted to analyze Treg differentiation and function. Results: No significant differences were found between resistant and sensitive patients in the percentage of CD4+ T cells and Tregs in PBMCs or the differentiation and function of induced Tregs (iTregs). However, iTregs from resistant patients presented higher monocarboxylate transporter (MCT) expression. Lactate induced more iTregs and improved OXPHOS levels in the resistant group. MCT1 and MCT2 were highly expressed in tumor-infiltrating Tregs, and patients with higher MCT1 expression had worse clinical outcomes. Combinatorial therapy with MCT antibody and anti-PD-1 therapy effectively inhibited tumor growth. Conclusion: MCT and its downstream lactate signal in Tregs can confer anti-PD-1 resistance and may be a marker of poor prognosis in HCC.